MnBi2Se4-based magnetic modulated heterostructures - Petrov, Evgeny K. (Magnetism)
Thin films of magnetic topological insulators (TIs) are expected to exhibit a quantized anomalous Hall effect when the magnetizations on the top and bottom surfaces are parallel and a quantized topological magnetoelectric effect when the magnetizations have opposite orientations. Progress in the observation of these quantum effects was achieved earlier in the films with modulated magnetic doping. On the other hand, the molecular-beam-epitaxy technique allowing the growth of stoichiometric magnetic van der Waals blocks in combination with blocks of topological insulator was developed. This approach should allow the construction of modulated heterostructures with the desired architecture. In the present paper, based on the first-principles calculations, we study the electronic structure of symmetric thin film heterostructures composed of magnetic MnBi2Se4 blocks (septuple layers, SLs) and blocks of Bi2Se3 TI (quintuple layers, QLs) in dependence on the depth of the magnetic SLs relative to the film surface and the TI spacer between them. Among considered heterostructures we have revealed those characterized by nontrivial band topology.